CHI '14 Extended Abstracts on Human Factors in Computing Systems 2014
DOI: 10.1145/2559206.2581260
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from ICT design of a healthcare worker-centered system for a chronic mental care hospital

Abstract: We report on our research on designing natural ICT tools and solutions for integration into a non-ICT based workflow at a Brazilian chronic care hospital. Our healthcare worker-centered approach for continuous lifecare contrasts from the more typical acute care situations where systems are geared towards a combination of patientcentered or administrator-centered designs. While acute care patients tend to spend a relatively short period of time in the hospital with life and death situations, chronic mental care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Appropriation is the term used by [3,4,6] in situations where the user creates new uses for technology solutions, thereby creating new requirements that must be considered by designers. During the appropriation process, users perceive more clearly their abilities, the best way to interact with technology solutions, how to adapt them to new uses and contexts, and how the users performs that in a better way.…”
Section: Contextualizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Appropriation is the term used by [3,4,6] in situations where the user creates new uses for technology solutions, thereby creating new requirements that must be considered by designers. During the appropriation process, users perceive more clearly their abilities, the best way to interact with technology solutions, how to adapt them to new uses and contexts, and how the users performs that in a better way.…”
Section: Contextualizationmentioning
confidence: 99%
“…By the end of this cycle, reports with interviews and observations, photos, movies, stories shading and creating scenarios were generated as artifacts. The research team involved in this first cycle reported their experiments and materials generated in dissertations and articles [1,3,6,4,5,7,8,10,11]. The second cycle of activities involved analysis of the collected requirements and their validation through interviews.…”
Section: Figure 1 Activities Of Interaction Designmentioning
confidence: 99%
“…Extensive research has shown that involving technical health workers in using and operationalizing the DHIS-2 platform for health data management can lead to expected health outcomes [14][15][16][17][18]. It remains unclear whether socio-demographic factors may influence such outcomes -to our knowledge, no studies are interested in learning the association between sociodemographic factors and the use of the DHIS-2 platform at this moment.…”
Section: Introductionmentioning
confidence: 99%